The Routledge handbook of language and superdiversity an interdisciplinary perspective - Creese, Angela; Blackledge, Adrian (Routledge Handbooks in Applied Linguistics, 2018)
The Routledge Handbook of Language and Superdiversity provides an accessible and authoritative overview of this growing area, the linguistic analysis of interaction in superdiverse cities. Developed as a descriptive term to account for the increasingly stratified processes and effects of migration in Western Europe, 'superdiversity' has the potential to contribute to an enhanced understanding of mobility, complexity, and change, with theoretical, practical, global, and methodological reach. With seven sections, the handbook includes 35 state-of-the art chapters from international authorities. The handbook adopts a truly interdisciplinary approach, covering cultural heritage, sport, law, education, business and entrepreneurship. This volume is key reading for all those engaged in the study and research of Language and Superdiversity within Applied Linguistics, Linguistic Anthropology and related areas.